ChemInform Abstract: Layered Compounds BaM2Ge4Ch6 (M: Rh, Ir and Ch: S, Se) with Pyrite‐Type Building Blocks and Ge—Ch Heteromolecule‐Like Anions. Issue 31 (5th August 2014) - Lei, Hechang; Yamaura, Jun‐ichi; Guo, Jiangang; Qi, Yanpeng; Toda, Yoshitake; Hosono, Hideo
Abstract The title compounds are prepared from mixtures of Rh or Ir, BaS or BaSe, Ge, and S or Se (h‐BN capsule, 5 GPa, 1473 K, 2 h).